God and Caesar: selected essays on religion, politics, and society - Pell, George (Coonor Court Publ. [u.a.], 2007)
Catholicism and democracy -- Law and morality -- The church and politics -- Catholicism and the architecture of freedom -- Catholicism and democracy -- Is there only secular democracy? -- Faith, reason, and life -- God, evolution, and consilience -- The role of the bishop in promoting the Gospel of life -- The case for God -- Theology and the university -- Human dignity, human rights, and moral responsibility